PEMBERDAYAAN MASYARAKAT MATRILINEAL DALAM UPAYA MENINGKATKAN KUNJUNGAN IBU HAMIL - Devi Syarief; Dewi Susilawati; Desi Wildayani; Dian Furwasyih; Fadella Noviarti; Yolanda Natasia; Novrita (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
West Sumatra Province is one of the provinces with coverage of pregnant women visiting (K4) only reaching 73%. This condition needs to be considered considering that the maternal health program is a priority program in health. Tanah Datar Regency has the lowest K4 coverage and tends to decline in the last three years. The results of observations of servants in Sungayang village showed that the low coverage of K4 was caused by the inability of pregnant women to decide for themselves when to visit health care facilities, ignorance and also the lack of support from family and community. The results of interviews with several community leaders, it is known that public support for the health of pregnant women is less than optimal. The solution offered is the development of matrilineal community participation through empowerment and participation. The results of this community service are in the form of published articles in the Abdimas journal, training modules, and increasing knowledge of community groups about the management of pregnant women